Program Pelatihan Sumber Daya Manusia Unggul Untuk Meningkatkan Mutu Lulusan Di Stie Latifah Mubarokiyah Tasikmalaya - Adi Robith Setiana; Ridwan Hakiki; Elsa Syukriani Pujiati (CV. SINAR HOWUHOWU, 2025)
Higher education institutions play a strategic role in producing excellent human resources (HR) who are ready to compete in the job market. However, there is still a gap between graduates’ competencies and industry needs. This community service program aims to improve the quality of graduates at STIE Latifah Mubarokiyah Tasikmalaya through superior HR training focused on developing soft skills (communication, leadership, problem solving) and hard skills (data analysis, digital marketing, financial management). The implementation method includes training needs analysis, workshops, case study simulations, mentoring, and evaluation through pre-test and post-test. The results show a 25–30% increase in students’ competencies, greater confidence in facing the job market, and positive feedback from industry stakeholders who assessed that graduates are more adaptable to workplace challenges. This program produced a training module that can be used sustainably and strengthened the relationship between higher education and industry through internship and recruitment collaborations. Therefore, superior HR training has proven effective in enhancing graduate quality and supporting the vision of higher education institutions to produce competitive human resources at local, national, and international levels.